Determinants of the profitability and producers’ preferences for quality cassava planting material in Cameroon - Dontsop-Nguezet, P.; Mbanda, A.C.S.; Ononino, J.C.; Fotso Kaute, A.; Tubene, S.L.; Bamba, Z.; Ntawuruhunga, P. (Elsevier, 2025)
Cassava is the second largest food crop in Cameroon and contributes significantly to food security in the country. However, its yield remains low compared to other similar agro-climatic regions. The use of cassava quality planting materials (CQPM) is recognized as one of the solutions to this problem, although their availability is limited. This study evaluates the profitability of producing CQPM and the adequacy between their supply and demand in the market. Data were collected from 264 cassava-tuber producers' households and 42 CQPM producers in the Center, South, and Littoral regions of Cameroon. The analysis shows that the production of CQPM is profitable, with a margin rate of nearly 60 %. However, among the ten most in-demand varieties preferred by cassava-tuber producer households, only three (i.e., 30 %) are supplied by CQPM producers, implying that 70 % of the varieties preferred and demanded by these producers are not supplied in the market by CQPM producers. Considering the effect of profitability on the match between supply and demand, it is observed that the margin rate has a non-linear relationship with the match. Furthermore, nearly 7 out of 10 households intended to purchase CQPM. Therefore, increasing cassava-tuber producers’ awareness about the importance of using CQPM is essential to stimulate demand and supply. Popularizing demonstration plots is also necessary for producers to become familiar with the improved varieties to be promoted. Finally, strengthening the capacities of CQPM producers in the multiplication of CQPM by competent institutions will be essential.